2014
DOI: 10.1177/0091552114555904
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Minority, Female, and Non-Traditional STEM Majors in the Online Environment at Community Colleges

Abstract: Using data from more than 2,000 community college science, technology, engineering, and mathematics (STEM) majors in the National Postsecondary Student Aid Study, this research investigates how ethnicity, gender, non-traditional student risk factors, academic preparation, socio-economic status, and English-as-second-language/citizenship status relate to online course enrollment patterns. Even after controlling for other factors, Blacks and Hispanics (Black and Hispanic men, in particular) were significantly un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 27 publications
(28 reference statements)
6
52
0
1
Order By: Relevance
“…G.P.A., for example, has been cited in some studies as being higher for students who take courses online (e.g. Xu & Jaggars, 2011), and the same as face-to-face in others (Wladis et al, 2015). The pattern observed in this study may explain why: while higher college G.P.A.…”
Section: Other Predictors Of Online Enrollment For Stem Majorssupporting
confidence: 50%
See 3 more Smart Citations
“…G.P.A., for example, has been cited in some studies as being higher for students who take courses online (e.g. Xu & Jaggars, 2011), and the same as face-to-face in others (Wladis et al, 2015). The pattern observed in this study may explain why: while higher college G.P.A.…”
Section: Other Predictors Of Online Enrollment For Stem Majorssupporting
confidence: 50%
“…Numerous profiles of online learners (not specific to STEM), have found they are more likely to be female (Dutton, Dutton, & Perry, 2002;Guri-Rosenblit, 1999;Halsne & Gatta, 2002;Jaggars & Xu, 2010;Moore & Kearsley, 2005;Qureshi, Morton, & Antosz, 2002;Shea & Bidjerano, 2014;Xu & Jaggars, 2011), and our prior research found that female community college students enroll in significantly disproportionately more online STEM courses than males when compared to face-to-face STEM enrollments (Wladis et al, 2015). Given that females are underrepresented in STEM and yet may be more drawn to online learning, online courses might provide an important point of entry for female students in STEM disciplines.…”
Section: The Changing Higher Education Landscapementioning
confidence: 88%
See 2 more Smart Citations
“…Two-year programs and transferring credits have become a popular topic in the literature as the skyrocketing cost of higher education leaves students scrambling for more economical means of reaching their goals, such as enrolling in either online courses (Wladis, Hachey, and Conway 2015) or face-to-face courses (Wang 2016) at community colleges. Surprisingly, Wang (2013) reports that while high school exposure to mathematics and science courses appears to be a strong influence on students seeking a 4-year STEM degree, the impact on community college beginners' STEM interests is much smaller.…”
Section: Two-year Transfersmentioning
confidence: 99%